Atlas of ultrasound-guided procedures in interventional pain management - Narouze, Samer N. (Springer, 2011)
This book is the first and definitive reference in the growing field of ultrasonography in pain medicine. Each chapter details all you need to know to perform a specific block. Comparative anatomy and sonoanatomy of the various soft tissues are featured, and tips and tricks for correct placement of the ultrasound probe and administration of the injection are described in detail. All the major peripheral nerve blocks are discussed as well as the various injections of the spine, pelvis, and musculoskeletal system.